A pilot study on the vacuum degree online detection of vacuum interrupter using laser-induced breakdown spectroscopy. (5th October 2016) - Wang, X H; Yuan, H; Liu, D X; Yang, A J; Liu, P; Gao, L; Ding, H B; Wang, W T; Rong, M Z
Abstract: Vacuum degree online detection of vacuum interrupter has been a great challenge for decades. In this letter, a novel approach based on laser induced breakdown spectroscopy (LIBS) was proposed to solve this tough problem, which is suitable for non-intrusive, electro-magnetic interference free and remote detection. The spectral lines of Cu, H, N and O elements from the interrupter shield were detected for a large gas pressure range from p   =  1  ×  10 −3 Pa to 1  ×  10 5 Pa. It was found that the spectral intensities of O and H increase monotonically with gas pressure, in contrast the spectral intensity of Cu first decreases slightly and then increases. Their intensity ratios, especially for that of Cu to O, change dramatically and monotonically with the gas pressure when p   ⩽  0.1 Pa, indicating that they can be used for determining the vacuum degree values. Spectral ratio method fundamentally reduces the influences of the possible variation in measuring distance and the laser power fluctuation, making LIBS a promising method for vacuum degree online detection of vacuum interrupters.